Soft Tissue Changes Associated with First Premolar Extractions in Kashmir Female Population - Khurshid, Syed Zameer; Qazi, Shazana Nazir; Zargar, Nazia Majeed (Journal of Orofacial Research, 2015)
Purpose: The purpose of study was to examine the effect of upper and lower incisor retraction on reduction of the profile and to record any correlation between dental and soft tissue parameters. Materials and methods: The study was a retrospective cephalometric study. A homogenized sample of 10 adult female orthodontic patients was selected from the local population. All patients were treated at a private practice using Pre Adjusted 0.022" slot edgewise appliance. Pretreatment and posttreatment lateral cephalograms were taken in natural head position with lips in relaxed position. Each lateral cephalogram was traced and a reference line was established (a constructed line perpendicular to Sella-Nasion minus 7° through Sella). Linear measurements were made with a from A’ point, upper incisor tip, mandibular incisor tip, most anterior point of upper lip, most anterior point of lower lip and B’ point. The angular measurements were the nasolabial angle, labiomental angle. Upper and lower lip thickness and interlabial gap parallel to the reference line were also measured. Results: All linear and angular measurements showed statistically significant (p < 0.05) changes except for changes in upper lip thickness, lower lip thickness, lower vermillion, B’ point and lower lip anterior. The Pearson’s correlation test showed a significant positive correlation between upper incisor retraction and upper lip position statistically significant decrease in the interlabial gap by 3.4 ± 2.5 mm (p < 0.001). Conclusion: On the basis of the results obtained from this study, it can be concluded that extraction of the four first premolars followed by the retraction of anteriors can be successful in reducing dental and soft tissue procumbency in adult females with bimaxillary protrusion in the local population